VOCATIONALIZING EDUCATION IN NIGERIA: CHALLENGES AND ENHANCEMENT STRATEGIES - David A. Alawa, Mercy, N. G. Akeke, Mary A. Iyam, Vitalis U. Eke, John B. Adie (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study examined challenges and enhancement strategies for the vocationalization of education in Nigeria. To achieve this, two research questions were asked and two hypotheses were formulated to guide the study. The study was carried out in Nigeria. Descriptive survey research design was used for the study. The study used a sample of 300 respondents comprising162 male and 138 female vocational educators purposively selected from public Universities in the six (6) geo-political zones of Nigeria. A triangulation technique involving mixed methods of data collection, that is, use of a structured questionnaire and focused group discussions was adopted for the study. The instruments were face validated by three experts in the field of vocational education with a reliability coefficient of 0.74 obtained through Pearson Product Moment Correlation analysis. Data collected was analyzed using weighted mean, standard deviation and independent t-test statistic from SPSS version 20 to answer the research questions and test the null hypotheses at p>.05. The study identified thirteen (13) challenges and eleven (11) strategies that could enhance the vocationalization of education. It was recommended that the identified challenges be addressed squarely and enhancement strategies adopted by government to ensure that education in Nigeria is fully vocationalized.